Genome-wide mapping of hot spots of DNA double-strand breaks in human cells as a tool for epigenetic studies and cancer genomics - Tchurikov, N.A. (Genom Data, 2015)
Hot spots of DNA double-strand breaks (DSBs) are associated with coordinated expression of genes in chromosomal domains (Tchurikov et al., 2011 [1]; 2013). These 50–150-kb DNA domains (denoted “forum domains”) can be visualized by separation of undigested chromosomal DNA in pulsed-field agarose gels (Tchurikov et al., 1988; 1992) and used for genome-wide mapping of the DSBs that produce them. Recently, we described nine hot spots of DSBs in human rDNA genes and observed that, in rDNA units, the hot spots coincide with CTCF binding sites and H3K4me3 marks (Tchurikov et al., 2014), suggesting a role for DSBs in active transcription. Here we have used Illumina sequencing to map DSBs in chromosomes of human HEK293T cells, and describe in detail the experimental design and bioinformatics analysis of the data deposited in the Gene Expression Omnibus with accession number GSE53811 and associated with the study published in DNA Research (Kravatsky et al., 2015). Our data indicate that H3K4me3 marks often coincide with hot spots of DSBs in HEK293T cells and that the mapping of these hot spots is important for cancer genomic studies.